2022
DOI: 10.3390/app12031230
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19′s Pandemic Effects on Bike Sharing Systems: A New Reality for Urban Mobility?

Abstract: On 11 March 2020, the World Health Organization made the assessment that a new disease (COVID-19) caused by a novel coronavirus (SARS-CoV-2) could be characterized as a pandemic. From that point, a chain reaction of events and difficult decisions requiring action was launched. National governments all over the world announced partial or total quarantine lockdowns in an effort to control the virus’ spreading in order to save as many lives as possible. The effects of the pandemic were multifaceted and transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In turn, France currently strongly focuses on the development of activities in the field of bicycle tourism and micro-mobility, hence the noticeable changes in bike-sharing systems. Moreover, trends indicate that the pandemic had a significant impact on the significant development of micro-mobility systems [96], which the conducted research reflects in the presented business models. In turn, Poland is a relatively new shared mobility market [97].…”
Section: Discussionmentioning
confidence: 81%
“…In turn, France currently strongly focuses on the development of activities in the field of bicycle tourism and micro-mobility, hence the noticeable changes in bike-sharing systems. Moreover, trends indicate that the pandemic had a significant impact on the significant development of micro-mobility systems [96], which the conducted research reflects in the presented business models. In turn, Poland is a relatively new shared mobility market [97].…”
Section: Discussionmentioning
confidence: 81%
“…Research on the post-pandemic reality indicates the effect of the pandemic on modal choice. Bouhouras et al [61] showed that residents of urban areas were more willing to change the means of transport used for their journeys (to a bike sharing system) during the pandemic. Their study showed that after the pandemic ended, the role of these means of transport in the post-pandemic reality had strengthened compared to pre-pandemic observations.…”
Section: The Impact Of the Pandemic On Urban Transport Behaviour And ...mentioning
confidence: 99%
“…BSS systems had become increasingly popular in many cities over the previous 20 years due to their beneficial effects on the users' health, the ability to combine them with other modes of public transport and their potential to reduce the use of motor vehicles and lower greenhouse gas emissions ( DeMaio, 2009 ). During lockdown, BSS services in Boston, Chicago and New York provided free access to health workers and other essential personnel to promote the use of bicycles as a means of transport during the pandemic ( Bouhouras et al, 2022 ), while some cities, such as Houston, Atlanta and New Orleans in the USA ( Miketa & Sun, 2020 ) and Santander, Spain, suspended their BSS service ( Aloi et al, 2020 ). Furthermore, in some cities, such as Bogotá, New York and Barcelona, bike lanes were extended, added to or made bike-friendly (or cyclable) streets.…”
Section: Bsss and The Covid-19 Pandemicmentioning
confidence: 99%